Predictive value of lactate levels for mortality in pneumonia: a systematic review and meta-analysis - Hu, Ziyun; Qiang, Yanfei; Yan, Xiaolin (The Journal of Infection in Developing Countries, 2025)
Introduction: Lactate levels, a marker of tissue hypoxia and metabolic acidosis, have been suggested as a prognostic indicator for patient outcomes in pneumonia. This systematic review and meta-analysis aim to determine the predictive value of lactate levels for mortality in patients with pneumonia. Methods: A systematic literature search was done using CINAHL, SCOPUS, EMBASE, MEDLINE, Cochrane, Google Scholar, and ScienceDirect databases. Random-effect models were used to calculate pooled effect estimates, including sensitivity, specificity, and diagnostic odds ratios. Heterogeneity, publication bias, and meta-regression analyses were performed. Results: A total of 17 studies were included. The pooled diagnostic odds ratio for lactate levels in predicting mortality was 5 (95% CI: 3-8). The sensitivity and specificity were 61% (95% CI: 52 - 69%) and 78% (95% CI: 73 - 82%), respectively. The positive and negative likelihood ratios were 2.7 (95% CI: 2.1-3.4) and 0.51 (95% CI: 0.40-0.64). The area under the receiver operating characteristic curve was 0.77 (95% CI: 0.72-0.82). Subgroup analysis showed that studies with lactate cut-off values between 1.2 and 2 mmol/L had better sensitivity, while studies with cut-off values greater than 2 mmol/L had higher specificity. Conclusions: Lactate levels have moderate predictive value for mortality in patients with pneumonia. This indicator may potentially aid in risk stratification and clinical decision-making. Further research is needed to determine optimal lactate cut-off values and evaluate the potential benefits of incorporating lactate monitoring into pneumonia management strategies.